(untitled) (Acta Scientiarum. Health Sciences, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.16741 Cardiovascular diseases are the main cause of death in world population. Current analysis with 1074 schoolchildren in municipal schools of Cruzeiro do Oeste, Paraná State, Brazil, evaluated anthropometric indexes and blood pressure levels of schoolchildren and verified the relationship between Body Mass Index (BMI) and Waist Circumference (WC) with blood pressure (BP). Evaluations comprised weight and height for the calculation of BMI, waist circumference and arterial pressure. Chi-square test and Cramer’s coefficient verified whether the variables were associated. High percentage of weight excess was reported, or rather, 16.6% of children were overweight; 9.8% were obese; 30.6% had high WC and 38.3% had high blood pressure. BMI and WC were associated with high BP. Overweight schoolchildren with central adiposity had a great trend of having high blood pressure.